2014
DOI: 10.1103/physrevlett.113.167202
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic Properties ofoLuMnO3Controlled byb-Axis Strain

Abstract: Strain is a leading candidate for controlling magnetoelectric coupling in multiferroics. Here, we use x-ray diffraction to study the coupling between magnetic order and structural distortion in epitaxial films of the orthorhombic (o-) perovskite LuMnO(3). An antiferromagnetic spin canting in the E-type magnetic structure is shown to be related to the ferroelectrically induced structural distortion and to a change in the magnetic propagation vector. By comparing films of different orientations and thicknesses, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
12
31
0
Order By: Relevance
“…There is a clear rise of B int between 75 and 50 K reaching a small plateau down to 40 K before rising a second time with a saturation of B int starting at 30 K. The transition starting between 75 and 100 K is associated with the appearance of FM order [22], and the plateau starting at ≈50 K would correspond to a saturation of the magnetic moment. The second transition observed ≈40 K agrees well with the onset of antiferromagnetism in LMO films and bulk [22][23][24]34]. It is important to note that a zero magnetic field μSR measurement provides a true microscopic confirmation of a magnetic ground state, i.e., the magnetic component is not induced by the application of an external magnetic field.…”
Section: A Magnetic Characterizationsupporting
confidence: 75%
See 2 more Smart Citations
“…There is a clear rise of B int between 75 and 50 K reaching a small plateau down to 40 K before rising a second time with a saturation of B int starting at 30 K. The transition starting between 75 and 100 K is associated with the appearance of FM order [22], and the plateau starting at ≈50 K would correspond to a saturation of the magnetic moment. The second transition observed ≈40 K agrees well with the onset of antiferromagnetism in LMO films and bulk [22][23][24]34]. It is important to note that a zero magnetic field μSR measurement provides a true microscopic confirmation of a magnetic ground state, i.e., the magnetic component is not induced by the application of an external magnetic field.…”
Section: A Magnetic Characterizationsupporting
confidence: 75%
“…1. These magnetization measurements therefore establish an onset of the FM order at relatively high temperatures independent of the AFM order observed below T ≈ 40 K [22,24]. In addition, the magnetization measurements show that the ferromagnetism in our films is relatively soft above T ≈ 40 K but becomes harder with decreasing temperatures.…”
Section: A Magnetic Characterizationsupporting
confidence: 65%
See 1 more Smart Citation
“…From the magnetic resonant diffraction we figured out that the ordering of Mn spins also differs significantly between the strained and the relaxed o-HMO films. 35,43,44 It is thus demonstrated that the compressively strained o-HMO films acquire two key differences in their multiferroic properties with respect to relaxed films and to bulk: an increased value of the T FE , and an enlarged magnetic modulation q b , which is pushed close to the commensurate E-type value of 0.5. It is reasonable to argue that these significant differences are a consequence of the modification of interatomic distances by epitaxial strain.…”
mentioning
confidence: 98%
“…For example, in multiferroic materials, the ferroelectric polarization is strongly coupled to the underlying crystal structure, which can be tuned by strain, and will affect the magnetization via magnetostriction. 8 Likewise, uniaxial strain can be utilized to alter magnetic exchange integral overlap along a specific direction, and thus introduce or enhance magnetic anisotropy. It has also been demonstrated that magnetic anisotropy in magnetocaloric materials results in the rotating magnetocaloric effect, which is believed to facilitate the implementation of magnetic cooling.…”
mentioning
confidence: 99%